Penerapan Model Pembelajaran Kooperatif Tipe STAD dengan Pendekatan Open Ended untuk Meningkatkan Kemampuan Berpikir Kreatif Peserta Didik Berbantuan Video Interaktif pada Materi Fungsi Trigonometri Kelas XI SMA Negeri 1 Langke Rembong - Nakul, Kresentia Gresela; Ekowati, Ch. Krisnandari; Blegur, Irna K. S. (Pendidikan Matematika FKIP Universitas Mataram, 2024)
This study is motivated by the lack of creative thinking skills of students in learning mathematics as well as one-way learning patterns from the teacher. The interview results confirmed that the creative thinking ability of students of SMA Negeri 1 Langke Rembong class XI MIPA is still relatively low. Therefore, the purpose of this study is to improve the creative thinking ability of students in class XI D SMA Negeri 1 Langke Rembong by applying the STAD type cooperative learning model and open-ended approach assisted by interactive video on trigonometric function material. The type of research used in this study is Classroom Action Research referring to the Kemmis & Mc Taggart model which is carried out in 2 cycles, where each cycle consists of 4 stages, namely: 1) Planning, 2) Implementation, 3) Observation, and 4) Reflection. The data collection techniques were observation, tests, and documentation while the data analysis was descriptive and qualitative. The results showed that the percentage of creative thinking ability of students in the innovative category of 7.14% in cycle 1 increased to 70.37% in cycle 2 of the 27 students' test results analyzed. The application of this learning approach and media learning model also increased the student activity score from 83.5 in cycle I to 100 in cycle II and the teacher activity score increased from 95 to 100 in cycle II. Thus, the application of the STAD-type cooperative learning model with an ended approach assisted by interactive video can improve the creative thinking ability of students of class XI D SMA Negeri 1 Langke Rembong on trigonometric function material.